Evaluation of CropSyst model for soil moisture and water productivity of wheat - KUMAR, RAMESH; YADAV, R. S.; KUMAWAT, AMIT; YADAVA, N. D.; RATHORE, V. S.; NANGIA, VINAY; PAREEK, N. K. (Journal of Soil and Water Conservation, 2022)
Wheat [Triticum aestivum (L.)] is the second most important food grain crop in India ranking next to rice contributing about 35% of the food grain production in India. It has significantly contributed towards the success of the green revolution and has greatly helped to transform our country from a situation of hand to mouth to being self-sufficient. Wheat is a good supplement for nutritional requirement of human body as it contains 10-12 per cent protein and 65-75 per cent carbohydrates. Its by-product (straw) is also used as dry fodder for animals. Limited moisture and improper nutrient management areconsidered as major limiting factors for achieving higherproductivity of wheat in arid region. To introduce improved production methods, knowledge is required on how the agro-ecosystem would respond to these alternatives. For this assessment, dynamic simulation models such as the crop soil simulation model CropSyst are useful tools. Keeping this in view, the study â€œEvaluation of CropSyst model for soil moisture and water productivity of wheatâ€ was conducted on farmers field at village Mainawali in Hanumangarh district of Rajasthan.The soils of the area are alluvial and calcareous in nature formed under arid and semi arid climate. The soils of site are brown to greyish brown and dark grey in colour, besides being calcareous and slightly alkaline in reaction having 67.7, 11.1 and 21.0% of sand, clay and silt, respectively in 0-15 cm soil depth with pH 8.09 and low soil organic mattercontent.The simulate yield of wheat were closer to the observed wheat yield. The total water applied in wheatwas 555.5 mm out of this 412.4 mm consumed in ET. Thus, ET constituted 88.51% of total water applied and deep drainage constituted 7.4% and rest 4% stored as residual soil moisture.